Kinetics of Phase Decomposition in Ti4AlN3 and Ti2Aln - A Comparative Diffraction Study - Pang, W.; Smith, R.; Peterson, V.; Low, It-Meng (Jim) (Wiley, 2011)
A method for determining the kinetics of and the activation energy for the thermal dissociation of Ti2AlN and Ti4AlN3 in vacuum using in-situ time-of-flight (ToF) neutron diffraction is described. We discuss the thermal stability and phase transitions in Ti2AlN and Ti4AlN3. The 4th order polynomial function of time [y(t)=At4+Bt3+Ct2+Dt+E] is used to describe the isothermal decomposition and to calculate the mean value of the reaction rate constant at 1400, 1450, 1500,and 1550 °C. The rate constants at these four temperatures are used to determine the activation energy for the decomposition of Ti4AlN3 and Ti2AlN in vacuum using the Arrhenius equation, which are found to be 410.8 ± 50.0 and 573.8 ± 130 kJ/mol, respectively.